2020
DOI: 10.1186/s40168-020-00824-x
|View full text |Cite
|
Sign up to set email alerts
|

A predatory myxobacterium controls cucumber Fusarium wilt by regulating the soil microbial community

Abstract: Background: Myxobacteria are micropredators in the soil ecosystem with the capacity to move and feed cooperatively. Some myxobacterial strains have been used to control soil-borne fungal phytopathogens. However, interactions among myxobacteria, plant pathogens, and the soil microbiome are largely unexplored. In this study, we aimed to investigate the behaviors of the myxobacterium Corallococcus sp. strain EGB in the soil and its effect on the soil microbiome after inoculation for controlling cucumber Fusarium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 83 publications
(112 reference statements)
2
78
0
Order By: Relevance
“…In cucumber, the myxobacterium Corallococcus sp. was found migrating toward the roots and root exudates of the cucumber plants via chemotaxis (Ye et al, 2020). In this study, the phenolic acid mixture secreted from the allelopathic rice could promote the production of secondary metabolites of the myxobacteria ( Supplementary Table S1), of which quercetin was determined as the main allelochemical, suggesting that it might interact with other toxic ketones and quinones to influence the herbicidal potential of the myxobacteria (Table 4).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In cucumber, the myxobacterium Corallococcus sp. was found migrating toward the roots and root exudates of the cucumber plants via chemotaxis (Ye et al, 2020). In this study, the phenolic acid mixture secreted from the allelopathic rice could promote the production of secondary metabolites of the myxobacteria ( Supplementary Table S1), of which quercetin was determined as the main allelochemical, suggesting that it might interact with other toxic ketones and quinones to influence the herbicidal potential of the myxobacteria (Table 4).…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies reported that myxococcales are known as metabolic factories and can produce a large number of secondary metabolites and can inhibit the germination of weeds and the proliferation of various harmful bacteria and fungi (Weissman and MĆ¼ller, 2009). Ye et al (2020) also documented that myxobacterium Corallococcus sp. strain EGB modified the FIGURE 6 | The effects of exogenously added quercetin on the growth of barnyard grass.…”
Section: Discussionmentioning
confidence: 99%
“…To construct the co-occurrence network of fungal genera in each treatment, only the abundant genera were used (the 50 most abundant). Because the data did not conform to the assumptions of the general linear model, significant correlations between any two genera were calculated using Networkx software ( ), with Spearmanā€™s | r| > 0.7 and a p -value < 0.05 following the previously described method ( Ye et al, 2020 ). Networks visualization was calculated with the interactive platform Gephi ( ).…”
Section: Methodsmentioning
confidence: 99%
“…can affect interactions with other microorganisms [66][67][68] while soil acidification caused by Rhizoctonia solani triggers changes in microbiome composition and activity [69] . The presence of the pathogen can also promote the reproduction of natural enemies such as viruses [70] , predatory bacteria [71] , and protists [72] , potentially triggering cascades in microbial trophic networks, which could feed back in the activation of plant immune responses.…”
Section: Detectionmentioning
confidence: 99%